Vitamin A deficiency in fattenning steers - ΤΣΑΚΑΛΩΦ Π.; ΒΛΑΧΟΣ Ν.; ΑΥΓΕΡΙΝΟΣ Σ. (Journal of the Hellenic Veterinary Medical Society, 2019)
In the present research work there are described cases of avitaminosis A observed in two herds of fattening steers. Diagnosis was established on the basis of history, the rations fed, the symptoms observed and determinations of the concentrations of vitamin A and carotene in the blood plasma. The rations fed and the symptoms observed are discussed. The importance of feeding fattening steers with good quality hay and of adding vitamin A supplements to their rations is emphasized